Influence of dye and nylon fibers on microwave-cured acrylic resin properties - FORTES,Carmen Beatriz Borges (2017)
ABSTRACT Objective: The aim of this study is to analyze if both color and nylon fibers have an influence on microwave-cured acrylic resin properties. Methods: Rectangular and disk-shaped specimens were prepared using acrylic resins; medium pink with and without nylon fibers and colorless without nylon fibers. To obtain the rectangular specimens, a stainless steel die was used with the following dimensions: 64 X 10 x 3 mm (± 0.5mm). To obtain disk-shaped specimens, a die 50mm (±0.5mm) in diameter and 0.5mm (±0.05mm) thick was employed. They were randomized to form groups: control (colorless acrylic) and experimental (medium pink, with and without nylon fibers), with each group consisting of ten (10) specimens rectangular in shape and five (5) disk-shaped. They were analyzed in six (6) assays (izod impact strength, n=10; Knoop hardness, n=10; glass transition temperature, n=3; water sorption and solubility, n=5; degree of monomer/polymer conversion, n=1; flexural strength and flexural modulus, n=10). All variables were subjected to the analysis of variance test followed by Tukey's multiple comparison test, at a 5% level of significance. Results: The analysis of the monomer/polymer degree of conversion did not reveal any difference between the three groups of resins (medium pink, with and without nylon fibers and colorless resin); it was approximately 88%. The results did not show significant differences between the groups for each variable (p>0.05). Conclusion: The results showed that color and presence of nylon fibers in acrylic resins did not affect the properties analyzed in this study.